Interactions Between Therapeutics for Metabolic Disease, Cardiovascular Risk Factors, and Gut Microbiota - Ding, Qi-You; Tian, Jia-Xing; Li, Min; Lian, Feng-Mei; Zhao, Lin-Hua; Wei, Xiu-Xiu; Han, Lin; Zheng, Yu-Jiao; Gao, Ze-Zheng; Yang, Hao-Yu; Fang, Xin-Yi; Tong, Xiao-lin (Frontiers in Cellular and Infection Microbiology, 2020)
With improved standards of living, the incidence of multiple metabolic disorders, including hyperglycemia and hyperlipidemia has increased year by year, especially (major risk factors for cardiovascular disease), continues to increase. Emerging epidemiological data and clinical trials have shown the additional protective eﬀects of some metabolic therapy drugs against cardiovascular diseases. A series of studies have found that these drugs may work by modulating the composition of gut microbiota. In this review, we provide a brief overview of the contribution of gut microbiota to both metabolic disorders and cardiovascular diseases, as well as the response of gut microbiota to metabolic therapy drugs with cardiovascular benefits. In this manner, we link the recent advances in microbiome studies on metabolic treatment drugs with their cardiovascular protective effects, suggesting that intestinal microorganisms may play a potential role in reducing cardiovascular risk factors. We also discuss the potential of microorganism-targeted therapeutics as novel treatment strategies for preventing and/or treating cardiovascular diseases and highlight the need to establish causal links between therapeutics for metabolic diseases, gut microbiota modulation, and cardiovascular protection.